Investigation of the association between the polymorphism SLC2A9 rs2280205 and gout in Vietnamese population - Ha, Do Thi Thu; Anh, Nguyen Phuong; Ngoc, Nguyen Thy; Duong, Nguyen Thuy (Vietnam Journal of Biotechnology, 2024)
Gout, a predominant form of inflammatory arthritis, is characterized by the deposition of uric acid crystals in joints and other tissues. Genome-wide association studies (GWAS) have established the association between gout and genetic variants of solute carrier family 2 member 9 (SLC2A9). In this study, we assessed the association of the single nucleotide polymorphism SLC2A9 rs2280205 with gout susceptibility in the Vietnamese population. Genomic DNA was extracted from the peripheral blood of 477 samples (160 gout patients and 317 healthy controls). The polymorphism rs2280205 of the SLC2A9 gene was genotyped using the PCR-RFLP method. Results indicated that the allele distribution of this variant was in accordance with Hardy-Weinberg Equilibrium, and the genotype frequencies of rs2280205 GG/GA/AA were 0.65, 0.33, and 0.02, respectively. However, no relation was identified between SLC2A9 rs2280205 and gout in this studied population. This research contributed a preliminary insight into the genetic factors in the development of gout in the Vietnamese population.